How Psychological Flexibility and Trust Shape Parenting Efficacy: A Quantitative Analysis - Gottschlich, Daniela (Journal of Psychosociological Research in Family and Culture, 2025)
Objective: This study aimed to investigate the predictive relationship between psychological flexibility, trust in relationships, and parenting efficacy. Methods and Materials: This study employed a correlational descriptive design with a sample of 350 parents, selected based on the Morgan and Krejcie table. Standardized measures, including the Parenting Sense of Competence Scale (PSOC), the Acceptance and Action Questionnaire-II (AAQ-II), and the Trust Scale, were administered to assess parenting efficacy, psychological flexibility, and trust in relationships, respectively. Data analysis was conducted using SPSS version 27, including Pearson correlation to assess bivariate relationships and multiple linear regression to examine the combined predictive effect of psychological flexibility and trust on parenting efficacy. Assumptions of normality, linearity, and multicollinearity were confirmed before conducting regression analyses. Findings: The results demonstrated that psychological flexibility was significantly correlated with parenting efficacy (r = 0.54, p < 0.01), as was trust in relationships (r = 0.47, p < 0.01). Multiple regression analysis indicated that psychological flexibility (B = 0.65, p < 0.01) and trust in relationships (B = 0.48, p < 0.01) were both significant predictors of parenting efficacy, accounting for 37% of its variance (R² = 0.37, p < 0.01). Psychological flexibility exhibited a slightly stronger predictive effect than trust in relationships. These findings highlight the importance of both individual cognitive adaptability and interpersonal trust in shaping parents’ confidence in their parenting abilities. Conclusion: This study provides empirical support for the significant role of psychological flexibility and trust in relationships in predicting parenting efficacy. The findings suggest that interventions aimed at enhancing parents’ emotional adaptability and strengthening relational trust may contribute to improved parenting confidence. Future research should explore longitudinal effects and cultural variations in these relationships to develop targeted parenting interventions.